2008
DOI: 10.1002/jts.20301
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of impending forced settler disengagement in Gaza: Trauma and posttraumatic growth

Abstract: The Israeli government's decision to remove settlers in the Gaza Strip forcibly produced a situation of traumatic stress, resulting from confrontation and conflict for settlers. The authors examined the effects of the Gaza disengagement, that occurred following prolonged terrorist exposure, on rates of probable major depressive disorder (MDD) and posttraumatic stress disorder (PTSD) diagnosis in a representative sample of Gaza settlers (N = 190). Predictors of probable MDD in multivariate models were being fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
121
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(134 citation statements)
references
References 34 publications
(49 reference statements)
10
121
3
Order By: Relevance
“…Some studies have reported a positive relationship (e.g., Wild & Paivio, 2003), whereas others have found a negative relationship (e.g., Hall et al, 2008), some a curvilinear relationship (e.g., Kleim & Ehlers, 2009), and others no relationship at all (e.g., Cordova et al, 2007;Salsman et al, 2009). Contradictory results of the impact of benefit finding on posttraumatic outcomes have been attributed to problems of measurement.…”
Section: Are Posttraumatic Changes Long Lasting?mentioning
confidence: 99%
“…Some studies have reported a positive relationship (e.g., Wild & Paivio, 2003), whereas others have found a negative relationship (e.g., Hall et al, 2008), some a curvilinear relationship (e.g., Kleim & Ehlers, 2009), and others no relationship at all (e.g., Cordova et al, 2007;Salsman et al, 2009). Contradictory results of the impact of benefit finding on posttraumatic outcomes have been attributed to problems of measurement.…”
Section: Are Posttraumatic Changes Long Lasting?mentioning
confidence: 99%
“…Estimates of posttraumatic stress disorder (PTSD) and depression among these populations vary. The following estimates of PTSD have been reported: 7% (Palmieri, Canetti-Nisim, Galea, Johnson, & Hobfoll, 2008), 21% (Shalev, Tuval, Frenkiel-Fishman, Hadar, & Eth, 2006), 26% (Hall et al, 2008), and 27% ). Estimates of depression vary from 17% (Hall et al, 2008) to 59% (Bleich, Gelkopf, & Solomon, 2003).…”
mentioning
confidence: 92%
“…The following estimates of PTSD have been reported: 7% (Palmieri, Canetti-Nisim, Galea, Johnson, & Hobfoll, 2008), 21% (Shalev, Tuval, Frenkiel-Fishman, Hadar, & Eth, 2006), 26% (Hall et al, 2008), and 27% ). Estimates of depression vary from 17% (Hall et al, 2008) to 59% (Bleich, Gelkopf, & Solomon, 2003). In a 2-year follow-up study of the effects of the Al Aqsa Intifada, Bleich and colleagues found a stable level of PTSD symptoms across two time points (9%), but a sharp decline in depression, from 59% (Bleich et al, 2003) to 29% (Bleich, Gelkopf, Melamed, & Solomon, 2006).…”
mentioning
confidence: 92%
“…Ultimately, the disengagement involved the forced uprooting in August 2005 of all the Israeli residents in Gaza-approximately 8,000 adults and children, who were compelled against their will (some forcefully) to leave their homes, communities and established local organizations permanently (MFA July 2005). decision at that time to implement a forced permanent evacuation of Israeli residents, despite their explicit desire and intention to continue living there, was a traumatic act for the people involved (Hall et al 2008), and stressful for the entire population in as much as Israeli soldiers had received an unprecedented order to carry out the operation by force. The TV coverage was difficult to reconcile even for those who supported the government decision.…”
Section: Introductionmentioning
confidence: 99%